Hepatitis B discrimination in everyday life by rural migrant workers in Beijing. Issue 5 (3rd May 2016) - Leng, Anli; Li, Youwei; Wangen, Knut Reidar; Nicholas, Stephen; Maitland, Elizabeth; Wang, Jian
ABSTRACT: Background : In China, the hepatitis B virus (HBV) is a particularly challenging public health issue, with an estimated 90 million chronic hepatitis B carriers accounting for almost 7% of the population. Health-related discrimination can serve as a barrier to prevention and care for infectious diseases, such as HBV, degrade the HBV sufferers' quality of life and limit HBV patients' employment opportunities. While rural migrants account for up to 40% of the total urban population in the developed cities in China, there has been no study of the discrimination behavior of rural migrant workers toward HBV carriers. Objective : This study evaluates the discrimination behavior of rural migrant workers toward HBV carriers and patients and proposes public policy recommendations to address discrimination and stigma. Methods : The sample comprised 903 rural adults, aged over 18 years old, who migrated to Beijing. Using a face-to-face interview, we surveyed rural migrants' demographic characteristics, knowledge of HBV and discrimination against HBV carriers. Descriptive statistics were used to characterize the study population, HBV stigma and knowledge of HBV. Three discrimination levels (no-mild, medium and severe discrimination) were modeled using multiple logistic regression. Results : Rural migrants to Beijing had a mean age of 36 years, were overwhelmingly married (91.58%), mostly with a junior high school or lower education (78.05%) and mainly engaged as temporary workers (42.52%) or self-employed (33.78%). Only 30.56% reported that they had been vaccinated against HBV. On the 0–10 discrimination scale, rural migrants rated 6.24, with only 4.54% displaying no sign of HBV-related discrimination. The high discrimination score occurred alongside a low mean knowledge of HBV (7.61 on the 1–22 ranking of HBV knowledge). Multiple logistic regression results suggest an inverse relationship between discrimination levels and HBV knowledge, especially knowledge about treatment and transmission routes. The "fear of being infected with HBV" and being HBV vaccinated was positively associated with HBV-related discrimination. Unemployed rural migrants were more likely to exhibit severe HBV-related discrimination than other occupational groups. Personal attributes, such as gender, age, marital status and education level were not associated with the level of discrimination. Conclusions : Knowledge of HBV, its transmission and treatment, and the fear of HBV infection were key features in understanding HBV discrimination by rural migrant workers. To reduce discrimination, HBV public health education campaigns need to focus on both knowledge about HBV and the fear of HBV infection. Such campaigns should target rural migrant subgroups, such as unemployed rural migrant workers.